Sistem Informasi Webstore Online Pada Toko DK Corner Menggunakan Metode Web Design Responsive Bootstrap - Ria Anggraini; Andri Andri (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2021)
Toko DK Corner is a trading company that specializes in selling women's daily fashion needs. Currently, the DK Corner Store records more than thousands of sales transactions every year, thus requiring the company to be able to provide ordering services for consumers to support better sales and service transactions and of course increase sales profits. The system development method used in system development is Web Engineering. To implement this sales and ordering information system, supporting components are needed in order to work properly. These components include using the PHP programming language (Personal Homepage), Bootstrap Framework and